Resuscitator’s perceptions and time for corrective ventilation steps during neonatal resuscitation() - Sharma, Vinay (Resuscitation, 2015)
BACKGROUND: The 2010 neonatal resuscitation program (NRP) guidelines incorporate ventilation corrective steps (using the mnemonic – MRSOPA) into the resuscitation algorithm. The perception of neonatal providers, time taken to perform these maneuvers or the effectiveness of these additional steps has not been evaluated. METHODS: Using two simulated clinical scenarios of varying degrees of cardiovascular compromise –perinatal asphyxia with (i) bradycardia (heart rate – 40 min(−1)) and (ii) cardiac arrest, 35 NRP certified providers were evaluated for preference to performing these corrective measures, the time taken for performing these steps and time to onset of chest compressions. RESULTS: The average time taken to perform ventilation corrective steps (MRSOPA) was 48.9 ± 21.4 s. Providers were less likely to perform corrective steps and proceed directly to endotracheal intubation in the scenario of cardiac arrest as compared to a state of bradycardia. Cardiac compressions were initiated significantly sooner in the scenario of cardiac arrest 89 ± 24 s as compared to severe bradycardia 122 ± 23 s, p < 0.0001. There were no differences in the time taken to initiation of chest compressions between physicians or mid-level care providers or with the level of experience of the provider. CONCLUSIONS: Effective ventilation of the lungs with corrective steps using a mask is important in most cases of neonatal resuscitation. Neonatal resuscitators prefer early endotracheal intubation and initiation of chest compressions in the presence of asystolic cardiac arrest. Corrective ventilation steps can potentially postpone initiation of chest compressions and may delay return of spontaneous circulation in the presence of severe cardiovascular compromise.